¿Qué es x si ln (x ^ 2) + ln (x ^ 3) + 2 = 0?

¿Qué es x si ln (x ^ 2) + ln (x ^ 3) + 2 = 0?
Anonim

Responder:

# x = raíz (5) (1 / e ^ 2) #

Explicación:

# 1 "" lnx ^ 2 + lnx ^ 3 + 2 = 0 #

Propiedad: # log_bm + log_bn = log_b (mn) #

# 2 "" ln (x ^ 2x ^ 3) + 2 = 0 #

# 3 "" ln (x ^ 5) + 2 = 0 #

Transfiere 2 al otro lado.

# 4 "" ln (x ^ 5) = - 2 #

# 5 "" log_e (x ^ 5) = - 2 #

Convertir a forma exponencial.

# 6 "" hArre ^ -2 = x ^ 5 #

# 7 "" raíz (5) (1 / e ^ 2) = raíz (5) (x ^ 5) #

# 8 "" color (azul) (x = raíz (5) (1 / e ^ 2)) #